A moderating effect of gender on the relationship between entrepreneurship educations, role of college, role model and inclination towards entrepreneurship: A study among Malaysian community college students - Ooi, Yeng Keat; Abdullahi, Nasiru (2015)
This study investigates the moderating effect of gender on the relationship between entrepreneurship education, role of college, role model and inclination towards entrepreneurship among Malaysian community college students. The sample consisted of 243 students from four community colleges who were the final year students in their diploma studies in various disciplines.A survey questionnaire was employed to obtain responses concerning their entrepreneurship inclination.The data was analysed using structural equation modelling (SEM) and employing the use Amos version 22. The results of the study showed that the role of college and role model have significant influence on entrepreneurial intention. Meanwhile, entrepreneurship education has no significance effect on intention. In addition, the influence of the control variable (experience) was also not significant.The study also found a significant difference in terms of gender in the relationship between role model, role of college and entrepreneurial intention. The relationship was found to be stronger for male than female in the role model and entrepreneurial intention, whereas the relationship between the role of college and entrepreneurial intention is stronger for female than male.The study, however, did not found significant difference of gender in the relationship between entrepreneurship education and entrepreneurial intention. We provide implications and recommendations for the outcomes of the study.